Enhancing Development Benefits to Local Communities from Hydropower Projects : A Literature Review - World Bank (Washington, DC, 2013)
The World Bank began a three-year pilot initiative to develop a framework for enhancing development benefits to local communities in hydropower projects. There has been a wide array of approaches in the past two decades that all have in common the objective of designing and implementing means and mechanisms to ensure local communities a more equitable share of project benefits. The World Bank intends to design and test a framework of enhancing development benefits that can be applied to hydropower projects and that can be tailored, at the same time, to the particular circumstances and characteristics of individual projects. This initiative is based on the hypothesis that hydropower projects planned in environmentally and socially sustainable manner can provide a large range of development benefits to local communities. Structure of this report: chapter one provides an introductory background to the literature review briefly explaining the current context of hydropower projects, the scope of the assignment and the structure of this report. Chapter two offers the core of the intellectual discussion by describing the approach and methodology utilized for the literature review, by describing the existing literature on benefit sharing in hydropower projects, by stating the constraints in enhancing development benefits and the existent gap in the literature. Finally, chapter three offers the main conclusions on the outcome of the literature review on enhancing development benefits to local communities.